Risk Management in Facing Macroeconomic Uncertainty on Pertamina's Profitability - Rastanura, Yudha; Priyarsono, Dominicus Savio; Ramadyanto , Widodo (International Journal Labs, 2025)
This study examines the effect of macroeconomic variables on the financial performance of PT Pertamina (Persero), a strategic Indonesian state-owned energy company (Badan Usaha Milik Negara/BUMN). Using time series data from 2005 to 2023, the research applies an econometric model examine relationship of macroeconomic variables between exchange rate, inflation, Bank Indonesia interest rate (BI Rate), and international crude oil prices (ICP) with corporate financial performance (Return on Equity/ROE and Return on Assets/ROA). Quantitative analysis is enhanced Montecarlo Simulation to model financial uncertainty and macroeconomic stress testing (moderate, pessimistic, optimistic scenarios). This study also integrates the risk management framework to construct a proses of risk management, and formulate data-driven risk mitigation strategies. The research is expected to contribute to the development of risk-informed financial management strategies based on econometric analysis and to serve as a reference for other BUMN in managing macroeconomic uncertainty.